Precise X-ray and video overlay for augmented reality fluoroscopy - Chen, Xin; Wang, Lejing; Fallavollita, Pascal; Navab, Nassir (International Journal of Computer Assisted Radiology and Surgery, 2013)
Purpose: The camera-augmented mobile C-arm (CamC) augments any mobile C-arm by a video camera and mirror construction and provides a co-registration of X-ray with video images. The accurate overlay between these images is crucial to high-quality surgical outcomes. In this work, we propose a practical solution that improves the overlay accuracy for any C-arm orientation by: (i) improving the existing CamC calibration, (ii) removing distortion effects, and (iii) accounting for the mechanical sagging of the C-arm gantry due to gravity. Methods: A planar phantom is constructed and placed at different distances to the image intensifier in order to obtain the optimal homography that co-registers X-ray and video with a minimum error. To alleviate distortion, both X-ray calibration based on equidistant grid model and Zhang's camera calibration method are implemented for distortion correction. Lastly, the virtual detector plane (VDP) method is adapted and integrated to reduce errors due to the mechanical sagging of the C-arm gantry. Results: The overlay errors are 0.38±0.06 mm when not correcting for distortion, 0.27±0.06 mm when applying Zhang's camera calibration, and 0.27±0.05 mm when applying X-ray calibration. Lastly, when taking into account all angular and orbital rotations of the C-arm, as well as correcting for distortion, the overlay errors are 0.53±0.24 mm using VDP and 1.67±1.25 mm excluding VDP. Conclusion: The augmented reality fluoroscope achieves an accurate video and X-ray overlay when applying the optimal homography calculated from distortion correction using X-ray calibration together with the VDP. © 2012 CARS.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Augmented reality; Calibration; Camera-augmented mobile C-arm; Homography; X-ray